Long Noncoding RNAs in Cell-Fate Programming and Reprogramming - Flynn, Ryan A.; Chang, Howard Y. (Cell stem cell, 2014)
In recent years, long noncoding RNAs (lncRNAs) have emerged as an important class of regulators of gene expression. lncRNAs exhibit several distinctive features that confer unique regulatory functions, including exquisite cell- and tissue-specific expression and the capacity to transduce higher-order spatial information. Here we review evidence showing that lncRNAs exert critical functions in adult tissue stem cells, including skin, brain, and muscle, as well as in developmental patterning and pluripotency. We highlight new approaches for ascribing lncRNA functions and discuss mammalian dosage compensation as a classic example of an lncRNA network coupled to stem cell differentiation. This Review discusses recent evidence showing that lncRNAs exert critical functions in adult tissue stem cells, developmental patterning, and pluripotency. The authors highlight new approaches for ascribing lncRNA functions and discuss mammalian dosage compensation as a classic example.